1994
DOI: 10.1042/bj2970615
|View full text |Cite
|
Sign up to set email alerts
|

Binding of Ca2+ to the (Ca2+-Mg2+)-ATPase of sarcoplasmic reticulum: equilibrium studies

Abstract: Equilibrium fluorescence methods have been used to establish a model for Ca2+ binding to the (Ca(2+)-Mg2+)-ATPase of skeletal muscle sarcoplasmic reticulum and to define the effects of H+ and Mg2+ on Ca2+ binding. The basic scheme proposed is: E2 <--> E1 <--> E1Ca <--> El'Ca <--> E1'Ca2. The E1 conformation of the ATPase initially has one high-affinity binding site for Ca2+ exposed to the cytoplasmic side of the sarcoplasmic reticulum, but in the E2 conformation this site is unable to bind Ca2+; Ca2+ does not … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0

Year Published

1994
1994
2006
2006

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(22 citation statements)
references
References 44 publications
1
21
0
Order By: Relevance
“…On the other hand, inhibition by vanadate and TG would result in locking the enzyme in a stable 'E2' conformation. Two characteristics of the EI-E 2 equilibrium are in favor of this scheme: the rate of Ez-E 1 is accelerated at basic pH [23][24][25] and by monovalent cations [6,26,27]. In addition the evaluation of the K ÷ or Na + flux rate gives a value of turn-over in the same range as the rate of the E2--+E1 conformational change.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, inhibition by vanadate and TG would result in locking the enzyme in a stable 'E2' conformation. Two characteristics of the EI-E 2 equilibrium are in favor of this scheme: the rate of Ez-E 1 is accelerated at basic pH [23][24][25] and by monovalent cations [6,26,27]. In addition the evaluation of the K ÷ or Na + flux rate gives a value of turn-over in the same range as the rate of the E2--+E1 conformational change.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, it can be shown that the K 0.5 for vanadate inhibition equals K V ϫ (1 ϩ 1/K 12 ), where K V is the dissociation constant describing vanadate interaction with E2, and K 12 is the E1-E2 equilibrium constant [E2]/[E1]. Because K 12 is ϳ1 for wild type under the conditions applied here at neutral pH in the absence of Ca 2ϩ (29,40), the K 0.5 for vanadate inhibition of wild type must be close to 2 ϫ K V , and the expected K 0.5 for vanadate inhibition of a mutant in which K 12 is increased 58-fold equals K V ϫ (1 ϩ 1/58) Ϸ K V , thus corresponding to a 2-fold decrease, relative to wild type.…”
Section: Camentioning
confidence: 99%
“…However, several partial reactions involving the cytoplasmic high affinity sites are unaffected by 20 -40 mM lumenal Ca 2ϩ (26,30,31), indicating that such a transition may not occur.…”
mentioning
confidence: 99%